Drivers of food acquisition practices among adolescents in suburban food environments of Lao People’s Democratic Republic - Thidatheb Kounnavong; Miho Sato; Christopher Turner; Elaine Ferguson; Hongkham Xayavong; Manithong Vonglokham; Sharon E Cox; Junko Okumura; Kazuhiko Moji (Global Health Action)
Background Dietary shifts among adolescents in low- and middle-income countries are exacerbating the double burden of malnutrition. Understanding the drivers of adolescent food acquisition and consumption practices and their lived experiences of the food environment is crucial for the effective development of targeted interventions and policies. Objective To explore drivers of food acquisition and consumption practices among adolescents from two suburban schools in the food environments of Phonhong District, Lao People’s Democratic Republic. Methods We implemented a Qualitative-Geographical Information System methodology, featuring participatory photography, follow-up photo-elicitation interviews and focus group discussions with 30 adolescents from April to July 2022. Thematic analysis triangulated key themes from photos, maps, and transcripts. Results Drivers of food acquisition and consumption included interactions across external, interpersonal, and intrapersonal domains. The six key themes were food availability and accessibility, product properties and convenience, peers and social media, caregivers and household practices, affordability, desirability, and autonomy, and perceptions, beliefs, and social norms. Consumption of ultra-processed foods was driven by the availability and accessibility of these affordable products in schools. By contrast, consumption of fruits and vegetables was driven by parental food practices at home. Conclusion A comprehensive multi-scalar approach is required to improve adolescent diets and nutrition in the suburban food environment of Lao PDR. This includes restricting the sale of ultra-processed foods in schools, promoting home gardening, increasing caregivers’ awareness and engagement with adolescents about the benefits of healthy food choices, and leveraging social media to encourage healthy eating behaviors.